The influence of tactical positioning on performance in world-championship freestyle swimming - Craig Staunton; Jesús J. Ruiz-Navarro; Peter Edholm; Dennis-Peter Born; Dennis-Peter Born (Frontiers in Sports and Active Living)
PurposeThis study examined tactical positioning and pacing in short-distance (100 m), middle-distance (200 m, 400 m) and long-distance (800 m, 1,500 m) freestyle events, focusing on the influence of race distance, competition round (HEAT vs. FINAL), and sex.MethodsRace data from multiple World Championships (2013–2023) were analyzed. Spearman's rank correlations (ρ) were calculated to examine rank stability across race distances, competition rounds, and sex. Additionally, lane distributions of Top3 finishers were analyzed to assess the impact of lane position on race outcomes.ResultsRank correlations increased progressively from the first to the final lap across all race distances (p < 0.05). Long-distance events exhibited earlier rank stabilization, with correlations reaching ρ ≥ 0.90 by 50% race completion, whereas middle-distance events showed greater positional variability throughout. Rank correlations were lower in FINALS than in HEATS (p < 0.05), indicating greater positional shifts in high-stakes races. No significant sex-based differences were observed (p > 0.05). Central lanes (4 and 5) were associated with the highest Top3 finish rates, while outer lanes (0, 1, 8, and 9) had the lowest, particularly in long-distance events.ConclusionFinals foster more dynamic race strategies, with increased positional changes. Rank stability was achieved at a relatively earlier proportion of the race in long-distance events compared to middle-distance events. By the final lap, rank stability converged across all distances, suggesting that race order was largely set before the last lap, emphasizing early tactical positioning over late-race surges. These findings offer insights into optimizing race tactics and pacing in elite swimming.